Dietary fibre and protein do not synergistically influence insulin, metabolic or inflammatory biomarkers in young obese Göttingen minipigs. Issue 7 (14th April 2021) - Xu, Yetong; Curtasu, Mihai Victor; Bach Knudsen, Knud Erik; Hedemann, Mette Skou; Theil, Peter Kappel; Lærke, Helle Nygaard
Abstract: The effects of dietary fibre (DF) and protein on insulin response, lipidaemia and inflammatory biomarkers were studied in a model experiment with juvenile obese Göttingen minipigs. After 20 weeks feeding on a high-fat fructose-rich low-DF diet, forty-three 30-week-old minipigs (31·3 (sem 4·0) kg body weight) were allocated to low- or high-DF and -protein diets for 8 weeks in a 2 × 2 factorial design. High DF contents decreased ( P = 0·006) while high protein increased ( P < 0·001) the daily gain. High protein contents increased fasting plasma concentrations of glucose ( P = 0·008), NEFA ( P = 0·015), ghrelin ( P = 0·008) and non-fasting LDL:HDL ratios ( P = 0·015). High DF increased ghrelin ( P = 0·036) and C-peptide levels ( P = 0·011) in the non-fasting state. High protein increased the gene expression of fructose-bisphosphatase 1 in liver tissue ( P = 0·043), whereas DF decreased fatty acid synthase expression in adipose tissue ( P = 0·035). Interactions between DF and protein level were observed in the expression of leptin receptor in adipose tissue ( P = 0·031) and of PPAR γ in muscle ( P = 0·018) and adipose tissue ( P = 0·004). In conclusion, high DF intake reduced weight gain and had potential benefit on β -cell secretory function, but without effect on the lipid profile in this young obese model. High dietary protein by supplementing with whey protein did not improve insulin sensitivity or lipidaemia, and combining high DF with high protein did not alleviate the risk of metabolic abnormalities.